Information Seeking and Utilization of Bebe’s Exercise Vlogs on YouTube among Audiences - Domkerngsak, Tassnee; Savagsuriyawong, Gaewganya (Journal of Humanities and Social Sciences, Rajapruk University, 2026)
The objectives of this study were: (1) to examine information-seeking behavior, (2) to investigate the utilization of Vlogs, and (3) to explore the relationship between information-seeking and utilization. This quantitative research employed a questionnaire with a sample of 400 participants. The research instrument was a structured questionnaire, and the statistical methods used included percentage, mean, and Pearson’s correlation coefficient, processed with statistical software. The findings revealed that the participants consistently watched Vlogs almost every week and continuously followed new content. They tended to watch for more than 15 minutes per session and paid close attention without skipping content, indicating purposeful and highly engaged media selection behavior. Regarding the utilization of Vlogs, viewers were able to apply the content from Bebe’s exercise Vlogs in various ways, such as scheduling workouts, practicing demonstrated routines, using Vlogs as a training guide, and gaining inspiration to seriously improve their health. The results of the correlation analysis showed a very high relationship (r = .873, p < .01) between information-seeking behavior and the utilization of Bebe’s exercise Vlogs. This implies that individuals who follow the content attentively and regularly are highly likely to apply it in real life, including exercising, adopting healthier behaviors, and sharing information with others.